Diagnostic and Prognostic Potential of Biochemical and Hematological Markers in Tobacco Users with Oral Pre-Cancer Lesions: Markers in Tobacco Users with Oral Pre-Cancer - Tagar, Muhammad Rafique; Ahmed, Arsalan; Mustafa, Muhammad; Ghauri, Muzaffar Qayum Khan; Aslam, Muhammad Aqeel; Tagar, Shakeel Ahmed; Ahsan, Shaharyar (Pakistan Journal of Health Sciences, 2024)
Oral Pre-Cancer Lesions (OPLs) including leukoplakia, erythroplakia, and submucous fibrosis denote biochemical and histopathologically altered changes in the oral mucosa marked by subcellular and structural anomalies evocating of potential for a malignant transformation, which is primarily caused by tobacco exposure. Early diagnosis is of paramount importance to halt the progression of premalignant lesions to high-grade dysplasia and even oral cancer. Objective: To find the diagnostic and prognostic potential of biochemical and haematological markers in Tobacco Users (TU) with OPL. Methods: PRISMA guidelines were followed to perform this systematic review. After retrieving 170 epidemiological studies published from 2013 to 2023, through multiple databases (PubMed, Google Scholar, Sci-hub, and Science Direct), 21 were included to determine the potential of biochemical and haematological markers in risk stratification and early detection of OPL. Results: According to the following systematic review, extracted data showed specific biochemical and haematological indicators that could serve as markers in risk stratification and early detection of OPL. The OPL group exhibited significantly higher levels of biochemical markers IL-6, IL-8, TNF-α, HCC-1, PF-4, FRR, TP, MDA, MMP-12, and Ceruloplasmin and hematological markers NLR, PLR, CRP, ESR, WBC, and low Hb as compared to the control group. Following risk stratification, a group with older age, tobacco association with OPL, and elevated levels of markers were categorised as a higher-risk group. Conclusions: The biochemical and haematological markers are potential promising markers in the early detection of OPL from malignant lesions with diagnostic and prognostic significance.